2019
DOI: 10.3390/en12214104
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Micro-Fractures on the Flow in Tight Oil Reservoirs Based on Pore-Network Models

Abstract: In this paper, the influence of micro-fractures on the flow of tight reservoirs is studied on the microscopic scale. Three-dimensional digital cores of fractured tight sandstone with varying fracture apertures, lengths, and dip angles are constructed using computed tomography (CT) scans. Pore-network models are built using the three-dimensional digital cores to simulate the flow in tight oil reservoirs. The effects of the micro-fracture aperture, length and dip angle on the pore-throat structure, single-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The seepage process in microfractures under high pressure grouting is as follows: the cement slurry enters the microfracture under the action of grouting pressure, and the grout flows into the fracture and exerts force on the fracture surfaces on both sides [14,41]. Microfractures are opened due to the grouting pressure, allowing more cement slurry to enter the fracture channels.…”
Section: Mathematical Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The seepage process in microfractures under high pressure grouting is as follows: the cement slurry enters the microfracture under the action of grouting pressure, and the grout flows into the fracture and exerts force on the fracture surfaces on both sides [14,41]. Microfractures are opened due to the grouting pressure, allowing more cement slurry to enter the fracture channels.…”
Section: Mathematical Model Establishmentmentioning
confidence: 99%
“…Under high in situ stress and strong mining stress, surrounding rock masses commonly contain large amounts of fractures, including large-and medium-sized fractures as well as microfractures (fracture opening d ≤ 0:1 mm) [12][13][14]. With large deformation and continuous rheology of the surrounding rock, fractures in the rock mass are prone to squeezing and closing.…”
Section: Introductionmentioning
confidence: 99%
“…Tight-oil reservoirs are widely distributed around the world (e.g., [1,2]) and become a new prospect of hydrocarbon exploration and development [3,4]. Compared with conventional reservoirs, tight-oil rocks exhibit low porosity and permeability, a complex pore structure, and higher clay content [5][6][7]. Theoretical and experimental studies have shown that their permeability depends on microcracks [8][9][10][11], which significantly affect fluid flow [12][13][14][15] and the elastic properties [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…After it is mixed with water, the cement particles are suspended in the slurry, forming a complex solid-liquid two-phase fluid. Due to the large particle size of the cement particles, the cement particles will block the entrance of the micro-fractures making it difficult to inject into the micro-fractures [13,14]. This phenomenon is called the percolation effect.…”
Section: Introductionmentioning
confidence: 99%